(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The objective of the research is to identify training needs for art education teachers at the intermediate stage in Jahra Governorate form their point of views, and know the differences between the teacher answers depending on variables: (years of experience, and qualification). The researcher adopted a descriptive analytical method, and the sample contained (65) members from Art Education, teachers in intermediate schools in Jahra Governorate. The researcher built a questionnaire which consisted of 34 items distributed on three dimension, and the most important results: - The results showed that the value of the overall average was (2.38).It is located within the appreciation of the high, which indicates the presence of the needs of a variety of training needs for education teachers of art, ranging from the planning of lessons , the academic side, artistic specialist, educational to the skill side.At the top of training needs comes the second aspect of the academic educational needs (learning theories – effective teaching strategies – growth characteristics of students in middle school- communication and treated Students – Methods of the modern calendar). - There are significant differences between the averages responses of teachers on the research questionnaire based on variable of qualification for qualified individuals who possess less scientific qualification. - There are significant differences between the averages responses of teachers on the research questionnaire based on the variable of years of experience in favour of individuals who have fewer years of experience. The research reached a number of suggestions, these are some important ones: - Organizing training programs for teachers of art education. They should be arranged and depend on the following training needs: aspects of the planning of education and the academic side of educational, artistic aspect and skills. - Preparing programs according to the art education teachers needs in schools. - Studying training needs for art education teachers each year.